Emotional Adjustment among Adolescent Students with and without Specific Learning Disabilities - Isaías Martín-Ruiz; María-José Go; Lidia Infante-Cañete (MDPI AG, 2023)
Adolescence is a psychologically vulnerable stage in which problems of emotional adjustment and psychological well-being can appear. The aim of this study is to analyse the relationship and comparison of emotional deficits and resources among adolescents with or without specific learning disabilities. We evaluated 80 students distributed into two groups: 40 adolescents with specific learning disabilities and 40 normative adolescents matched with the previous group in terms of age, sex, and school year. The study variables are internalising problems (anxiety and depression), externalising problems (aggression, anger control, defiant behaviour, and antisocial behaviour), and personal resources (self-esteem, social competence and integration, and awareness of problems), evaluated by means of the SENA test. The results indicate a positive relationship between externalising and internalising problems and a negative relationship between the latter and some personal resources in both groups. We also found that adolescents with specific learning disabilities displayed more internalising and externalising symptoms than their peers, greater awareness of their emotional difficulties, and lower self-esteem and social integration and competence. The findings highlight the need for preventive interventions that promote the psychological well-being and mental health of adolescents within the school setting at an early age.